1989
DOI: 10.1021/bi00437a035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lung major GTP-binding protein as Gi2 and its distribution in various rat tissues determined by immunoassay

Abstract: Antisera were raised in rabbits against the 40-kDa alpha subunit of bovine lung GTP-binding protein, which were identified as the alpha subunit of Gi2 (Gi2 alpha) by the analysis of the partial amino acid sequence. Antibodies were purified with a Gi2 alpha-coupled Sepharose column and then were passed through a Gi1 alpha-coupled Sepharose column to remove antibodies reactive also with 41-kDa alpha. Purified antibodies reacted with Gi2 alpha, but not with Gi1 alpha, Gi3 alpha, or Go alpha in an immunoblot assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
2

Year Published

1990
1990
1997
1997

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
5
33
2
Order By: Relevance
“…However, G, is located predominantly in the nervous tissues and neuroendocrine cells, while Giz is located in all tissues [30,31]. In the brain, the level of G, was about 15-fold higher than that of Gi2, and the concentrations of Gi2 were constant throughout ontogenic development, while the G, levels markedly increased coincidently with neural development [3 11.…”
Section: Discussionmentioning
confidence: 99%
“…However, G, is located predominantly in the nervous tissues and neuroendocrine cells, while Giz is located in all tissues [30,31]. In the brain, the level of G, was about 15-fold higher than that of Gi2, and the concentrations of Gi2 were constant throughout ontogenic development, while the G, levels markedly increased coincidently with neural development [3 11.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of G␣ o in cardiac myocytes is 30-to 120-fold lower than in brain (25,26). Unlike the brain, in the rat heart, the G␣ o is not the major G␣ subunit expressed.…”
mentioning
confidence: 88%
“…In rat heart, the amount of G␣ s is 0.2 g per mg of protein, while G␣ o is 0.06 g per mg of protein (25). G␣ o is half as abundant as its close relative, G␣ i2 (26). It has not been clear whether it specifically regulated any pathway, nor how redundant is its function with other, more abundant G␣ subunits.…”
mentioning
confidence: 99%
“…The molecular cloning and sequence analysis of cDNAs have shown that G i has three forms of the α subunit: G i1 α, G i2 α, and G i3 α (Hepler and Gilman 1992). The α subunits of G i1 and G o are widely distributed in the neuropil of the rat brain (Worley et al 1986;Asano et al 1987Asano et al , 1989Terashima et al 1988) and the concentration of G o α in the nervous tissues gradually increases after birth (Asano et al 1988a), while the concentration of G i2 α is constant throughout development (Asano et al 1989). …”
Section: Introductionmentioning
confidence: 99%